(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article examines the essence of realism as a literary movement. During my research, I learned and found out that realism is a true portrayal of reality. The essence of realism is the representation of life in images that correspond to the phenomena of real life. Literature for realism is a means of cognition of man and the world, therefore, it strives for a wide coverage of life, illumination of all its sides without restriction; in the center of attention is the interaction of a person and the social environment, the influence of society conditions on the formation of personality. The category "realism" in a broad sense defines the relationship of literature to reality in general, regardless of which trend or direction in literature a given author belongs to. Any work in one way or another reflects reality, but in some periods of the development of literature there was an orientation towards artistic convention. But the demand for verisimilitude does not mean abandoning the means of artistic convention. The art of the writer consists in the ability to concentrate reality, drawing heroes, which, perhaps, did not exist in reality, but in which real people like them were embodied. Realism in the narrow sense was formed as a trend in the 19 th century